Handling Bullying Behavior Based on Friday Worship at the Aisyiyah Sungguminasa Gowa Islamic Senior High School - Aripuddin Aripuddin; Faridi Faridi; Sunarto Sunarto (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to analyze efforts to overcome bullying behavior based on Friday prayers at Madrasah Aliyah Aisyiyah Sungguminasa. In terms of application and implementation, using Bandura's social theory perspective. The research approach used was descriptive qualitative with a case study method. Data collection was carried out through observation, interviews, and documentation techniques. Data were analyzed through three stages: data reduction, data presentation, and conclusion drawing. Data validation was tested through triangulation of data sources and collection techniques. The results of the study indicate thatThe Friday Worship program has significant implications for shaping student character and addressing bullying at Madrasah Aliyah Aisyiyah Sungguminasa. This activity has raised students' awareness of the negative impacts of bullying on both victims and perpetrators. Furthermore, the religious atmosphere fostered through Friday Worship creates a more conducive madrasa environment, one filled with tolerance and empathy. Students have demonstrated positive behavioral changes, such as increased concern for their peers, reduced interpersonal conflict, and a growing culture of mutual respect.